Detecting Tax Aggressiveness through Profitability, Leverage, Inventory Intensity and Company Size - Harnovinsah, Harnovinsah; Amyulianthy, Rafrini Amyulianthy; Permana, Erwin (AKRUAL: JURNAL AKUNTANSI, 2025)
Objectives: This study aims to examine the effect of profitability, leverage, inventory intensity, and firm size on tax aggressiveness in manufacturing companies listed on the Indonesia Stock Exchange during the 2021–2023 period. Tax aggressiveness is measured using the Cash Effective Tax Rate (Cash ETR). Methods: A quantitative approach was employed using multiple linear regression to test the proposed hypotheses. Results: The results show that profitability has a significant negative effect on tax aggressiveness, while leverage and firm size exhibit significant positive effects. Inventory intensity does not show a significant relationship. These results align with legitimacy theory, agency theory, and political cost theory in explaining internal corporate motivations for tax planning strategies. Implication: Practically, this study provides implications for tax authorities to focus on high-leverage and large-scale entities, and to promote fiscal transparency through risk-based tax supervision. Theoretically, this research contributes to the growing body of literature on corporate tax avoidance in developing countries, especially through the use of alternative indicators such as Cash ETR and BTD.